Magnetic resonance guided high intensity focused ultrasound for uterine fibroids and adenomyosis has no effect on ovarian reserve. (31st December 2023) - Otonkoski, Saara; Sainio, Teija; Mattila, Sami; Blanco Sequieros, Roberto; Perheentupa, Antti; Komar, Gaber; Joronen, Kirsi
Abstract: Introduction: Uterine fibroids are the most common benign tumors in healthy women. High Intensity Focused Ultrasound (HIFU) is a modern, noninvasive thermal ablation method for treating uterine fibroids. There is increasing evidence that ultrasound guided HIFU (US-HIFU) has no adverse impact on ovarian reserve but little data exists on magnetic resonance guided HIFU (MR-HIFU). There are different options to estimate ovarian reserve, perhaps the most reliable being the measurement of serum Anti-Müllerian hormone (AMH). Material and methods: Seventy-four (74) premenopausal women with serum AMH 0.1 ug/L or over, aged 24–48 and with fibroids or adenomyosis treated with MR-HIFU were enrolled in our study. AMH levels were analyzed before and 3 months after the MR-HIFU treatment. Correlations between AMH level changes and position of fibroids, fibroid volume, non-perfused volume ratio, and treatment energies were studied. Results: The median AMH level before the HIFU treatment was 1.20 (range: 0.1–7.75 ug/L) and after the treatment 1.23 (range: 0.1–8.51 ug/L). No significant change was detected ( p = .90). The patients were divided in three subgroups depending on the baseline AMH levels. The changes were not significant in any of the subgroups. Neither did the location of the treated fibroid affect the change of AMH levels nor the total energy used during treatment. Conclusions: MR-HIFU does not compromise the ovarian reserve. Neither the location of the treated fibroid nor the total energy used during MR-HIFU had any effect on the change of AMH levels.